A Small Homeland and a Large Book - Kubalica, Tomasz; Noras, Andrzej J. (Folia Philosophica, 2022)
This text is an introduction to the philosophy of Heinrich Rickert. The introduction has three levels: biographical, bibliographical, and doxographic. The doxography involves examining Rickert’s views in the context of the achievements of Neo-Kantianism, the Baden school and contemporary philosophy. Noras discusses the main issues Rickert treated in his philosophy, which was occupied with the theory of cognition, the methodology of the humanities and natural sciences and the philosophy of the history of philosophy.